(untitled) (CIPEEX, 2026)
Vulvodynia is a chronic vulvar pain condition, with multifactorial origin, that compromises the quality of life of adult women. The aim of this study was to investigate the effectiveness of physiotherapeutic interventions in the management of the condition through an integrative literature review in the PubMed, SciELO, LILACS, and Google Scholar databases (2015–2025), including women aged 18 to 59 years. Techniques such as kinesiotherapy, myofascial release, biofeedback, electrostimulation, and educational strategies demonstrated effectiveness in reducing pain, improving function, and restoring sexuality. The combination with psychological support and a multidisciplinary approach enhanced the outcomes. It is concluded that pelvic physiotherapy represents an effective non-pharmacological alternative, highlighting the need for the development of evidence-based clinical protocols and continuous training of health professionals. Keywords: vulvodynia; pelvic physiotherapy; vulvar pain; quality of life.